A Case Study of Instructional Contributions of Community and Government Secondary School Administrators in Pakistan - Khan, Asif (Journal of Education and Vocational Research, 2013)
The study examined the instructional contribution of a community and government school administrator in Pakistan. While using qualitative tools to generate data, the research exclusively examined the administrators’ engagements in such instructional processes as conducting class visits, arranging inschool professional development programs, and contributing to curriculum enrichment. The study noted that as compared to government administrator, the community administrator seemed more active in the instructional processes of his school. The detachment of the government administrator from classroom practices had many implications that also influenced the quality of education in the government school. On the basis of the findings of this study, I maintain that the efficiency of school administrators is contingent upon multiple elements, such as provisions of job related training, introduction of an effective accountability tool, support of instruction oriented educational officials, and contribution of community/parents The study suggested Pakistan should address the above-mentioned elements when defining the instruction-oriented role of school administrators in the country.